2003
DOI: 10.1007/s00421-003-0923-2
|View full text |Cite
|
Sign up to set email alerts
|

Limiting factors to oxygen transport on Mount Everest 30�years after: a critique of Paolo Cerretelli?s contribution to the study of altitude physiology

Abstract: In 1976, Paolo Cerretelli published an article entitled "Limiting factors to oxygen transport on Mount Everest" in the Journal of Applied Physiology. The paper demonstrated the role of cardiovascular oxygen transport in limiting maximal oxygen consumption (VO2max). In agreement with the predominant view of VO2max limitation at that time, however, its results were taken to mean that cardiovascular oxygen transport does not limit VO2max at altitude. So it was argued that the limiting factor could be in the perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
1
17
1
1
Order By: Relevance
“…35,36 Contrasting this regulatory process in immune cells at high altitudes and in sepsis is the loss of mitochondrial structure -rather than functional change of the mitochondrial activity -in muscle cells at high altitudes. [25][26][27][28][29] In our study, antioxidant dietary supplements did not have any effect on the observed mitochondrial abnormalities. In human subjects at high altitude, results of trials on antioxidative treatment have shown mixed results.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…35,36 Contrasting this regulatory process in immune cells at high altitudes and in sepsis is the loss of mitochondrial structure -rather than functional change of the mitochondrial activity -in muscle cells at high altitudes. [25][26][27][28][29] In our study, antioxidant dietary supplements did not have any effect on the observed mitochondrial abnormalities. In human subjects at high altitude, results of trials on antioxidative treatment have shown mixed results.…”
Section: Discussioncontrasting
confidence: 58%
“…Examining subjects before and after high-altitude exposure, different authors found decreases in enzyme activities of aerobic-oxidative metabolism which were related to decrements in mitochondrial volume density, suggesting a cellular loss of mitochondrial structure rather than qualitative changes of the mitochondrial function. [25][26][27][28][29] In these subjects, significant reduction of muscle-fiber cross-sectional area, and an unchanged capillary-to-muscle-fiber ratio and therefore increased capillary density, have been reported. The effect of hypoxic exposure on citrate synthase activity which is a marker of mitochondrial volume density and oxidative capacity remains controversial.…”
Section: Discussionmentioning
confidence: 95%
“…Mitochondrial volume density is consistently and substantially decreased in the skeletal muscle of climbers acclimatizing to high altitude [12,13], and was found to be lower in the muscles of Himalayan Sherpas than those of unacclimatized lowlanders [13]. Prolonged exposure to altitude is also associated with accumulation of lipofuscin in skeletal muscle [14], a lipid peroxidation product that may be indicative of mitochondrial damage.…”
Section: Regulation Of Mitochondrial Volume and Redox Homeostasismentioning
confidence: 99%
“…In particular, structural and functional remodeling of the mitochondria has emerged as a critical component of hypoxic survival (24, 53, 55). Mitochondrial volume density has been observed to decrease with chronic hypoxia in a range of adult vertebrates, and this is often associated with large-scale reductions in ETC Complex activities and aerobic capacity (15, 21, 24, 25, 33, 34, 42, 55, 56). Mitochondrial efficiency can be improved by CIV subunit switching which maximizes the yield of ATP per oxygen molecule consumed and minimizes the production of harmful ROS (23).…”
mentioning
confidence: 99%